LEISURE AND SPORTS EQUIPMENT IN THE CITY OF BARRA DO GARÇAS, MATO GROSSO, BRAZIL (Fiep Bulletin - online, 2016)
This study presents a panorama of the distribution of public leisure and sports spaces and the corresponding equipment in the city of Barra do Garças, MatoGrosso. It is a qualitative and exploratory study, in which we identify unequal distribution of such spaces in the city, with a concentration in the central regions. The findings provide support for planning and implementing public policies for better distribution of leisure and sports equipment.
Keywords: Leisure and sports equipment; public policies; cities.